LncRNA FEZF1-AS1 Promotes TGF-β2-Mediated Proliferation and Migration in Human Lens Epithelial Cells SRA01/04 - Yong Wang; Lili Chen; Yonghui Gu; Ying Wang; You Yuan; Qiujian Zhu; Mingchao Bi; Shuyan Gu (Journal of Ophthalmology)
Posterior capsule opacification (PCO) is a common complication after cataract surgery attributed to the proliferation and migration of postoperative residual lens epithelial cells (LECs). The long noncoding RNA (lncRNA) FEZ family zinc finger 1 antisense RNA 1 (FEZF1-AS1) promotes the proliferation and migration of multiple types of cancer cells. Here, we discovered that FEZF1-AS1 is markedly upregulated in TGF-β2-treated SRA01/04 cells. In addition, the proliferation and migration of SRA01/04 cells were enhanced following TGF-β2 treatment. FEZF1-AS1 knockdown inhibited the TGF-β2-induced proliferation and migration of SRA01/04 cells. Accordingly, FEZF1-AS1 overexpression promoted the TGF-β2-induced proliferation and migration of SRA01/04 cells. Finally, FEZF1-AS1 upregulated TGF-β2-induced SRA01/04 cell proliferation and migration via boosting FEZF1 protein levels. Our findings indicate that the dysregulation of FEZF1-AS1 participates in the TGF-β2-induced proliferation and migration of human lens epithelial cells (HLECs), which might be achieved, at least in part, through the induction of FEZF1 expression.